Crop Loss Caused by the Root-Knot and Reniform Nematodes in Brinjal and Control of the Pests - Jiji T (Department of Agricultural Entomology, College of Horticulture, 1986)
Two pot culture experiments were laid out i) to study the pathogenic effect of different inoculam levels of root-knot and reniform nematodes on brinjal, alone or in combination each at 100, 500 and 1000 nematodes/plant comprising 10 treatments and 10 replications and ii) to study the effect of four granular chemicals viz. carbofuran, aldicarb, phorate and quinalphos at the rate of 1.0 and 1.5 kg ai/ha against the above two nematodes alone or in combination, comprising of twentyfive treatments and five replications. The results brought forth the adverse effect induced by the highest inoculum levels of two nematodes either alone or in combination on plant growth characters of brinjal even after 45 days of inoculation. The reniform nematode seems to have more pathogenic effect than root-knot nematode at the same inoculum level. The results obtained from the second experiment indicated that carbofuran or aldicarb at the rate of 1.0 and 1.5 kg ai/ha were found to be the best treatments resulting in increase in plant growth characters and yield and in reducing the nematode population in roots and soil. Phorate and quinalphos were found least effective in promoting growth of plants and in reducing nematode infestations. However the application of phorate or quinalphos at the rate of 1.5 kg ai/ha was found to have equal effect as that of carbofuran or aldicarb up to 15 days of their application.